Pathological and Molecular Investigation of Some Bacterial in the Lungs and Livers of Red Sokoto Goats Slaughtered at Ilorin, Kwara State, Nigeria. - Adam, Mohammed; Akeem, Ahmed Olayiwola; Barka, Sanni Abdul; Olu, Shoyinka Shodeinde Vincent; Abiodun, Ajadi Abdullateef; Ola-Fadunsin, Shola David (Universitas Airlangga, 2023)
This study was conducted to determine the pathological findings and molecular investigation of bacteria flora associated with the lesions in the lungs and livers of goats slaughtered for public consumption at the Ilorin, abattoir. A total of 450 samples (240 lungs and 210 livers) were collected and examined from goats slaughtered at the Ipata slaughterhouse in Ilorin, Kwara State. Of this number, 58 (24.17%; 95% CI = 19.19–29.96) lungs and 17 (8.10%; 95% CI = 5.17–12.58) livers revealed gross and microscopic pathological lesions as a result of bacterial pathogens. Based on gross examination, lung lesions were categorized into bronchopneumonia (27.59%), congestion (22.41%), interstitial pneumonia (17.24%), hemorrhages (13.77%), emphysematous (10.34%), and hyperemia (8.62%). In the liver, hepatic congestion 8 (47.06%) was the most observed gross lesion. Others included hepatic enlargement (29.41), hepatic fibrosis (17.65%), and hepatic abscess (5.88%). The molecular investigation revealed lung pathological lesions were as a result of Klebsiella species (51.72%) and Bacillus species (48.28%), while Escherichia species (52.94%) and Salmonella species (47.06%) were detected in the liver. The molecular analysis showed that the bacteria organisms detected in this study did not fully cluster with similar species from other parts of the world. The infection caused by these bacteria showed histopathological lesions in the lungs and livers. There is need for more studies to further characterize these bacteria species detected from Red Sokoto breeds of goats in-depth.